Carbonizing technology enables Sanguisorbae Radix to inhibit yeast-to-hypha differentiation and biofilm formation in Candida albicans - Xuxi Cheng; Jinyun Song; Qinglian Hu; Hongdan Wu; Bohui Song; Ruixiao Ma; Jinghan Gao; Yiwei Wang; Huangjin Tong; Wei Gu; Hongyu Zhao (PLoS ONE, 2025)
Sanguisorbae Radix (SR) has been employed as an herbal medicine over centuries. Charred SR (CSR), acquired via carbonization after the charred stir-frying of SR, demonstrates superior antimicrobial activity compared to SR. The aim of the study was to identify how carbonizing technology enhanced the ability of SR to inhibit the transformation from yeast to hypha and biofilm formation in C. albicans. In this paper, a vulvovaginal candidiasis (VVC) mouse model was used to evaluate the therapeutic effects. After CSR treatment, VVC mouse models nearly eliminated hyphal C. albicans adhering to the vaginal mucosa. The inhibitory activities of CSR on C. albicans biofilm formation and hyphal growth were assessed through quantitative biofilm analysis, morphological observations, and gene expression studies in vitro. Since the hyphal form signifies the initiation of biofilm development, this study confirmed CSR’s remarkable inhibitory effect on C. albicans biofilm formation and hyphal growth. These effects were significantly weaker with SR. Additionally, the impact of carbonization on the composition of active compounds was analyzed. Carbonization significantly increased the content of ellagic acid (EA) and pyrogallic acid (PYG) by 7.44-fold and 28.09-fold, respectively. Both EA and PYG inhibited C. albicans biofilms and hyphal growth, with EA showing a more pronounced inhibitory effect. Finally, we concluded that carbonization technology enables SR to inhibit the yeast-to-hypha transition and biofilm formation in C. albicans by increase the levels of EA and PYG. EA was identified as the primary bioactive compound responsible for CSR’s anti-biofilm effects.